The Effectiveness of Noninvasive Interventions for Temporomandibular Disorders: A Systematic Review by the Ontario Protocol for Traffic Injury Management (OPTIMa) Collaboration. Issue 3 (March 2016) - Randhawa, Kristi; Bohay, Richard; Côté, Pierre; van der Velde, Gabrielle; Sutton, Deborah; Wong, Jessica J.; Yu, Hainan; Southerst, Danielle; Varatharajan, Sharanya; Mior, Silvano; Stupar, Maja; Shearer, Heather M.; et al.
Abstract : Objective: To determine the effectiveness and cost-effectiveness of noninvasive interventions for temporomandibular disorders (TMD). Methods: We systematically searched MEDLINE, EMBASE, CINAHL, PsycINFO, and Cochrane Central register from 1990 to 2014 for effectiveness studies and the Cochrane Health Technology Assessment Database, EconLit, NHS Economic Evaluation Database, and Tufts Medical Center Cost-Effectiveness Analysis Register from 1990 to 2014 for cost-effectiveness studies. Random pairs of independent reviewers critically appraised eligible studies using the Scottish Intercollegiate Guidelines Network criteria. Evidence from eligible studies was synthesized using best-evidence synthesis methodology. Results: Our search for effectiveness studies yielded 16, 995 citations; 31 were relevant and 7 randomized controlled trials (published in 8 articles) had a low risk of bias. We found no relevant cost-effectiveness studies. The evidence suggests that for persistent TMD: (1) cognitive-behavioral therapy and self-care management lead to similar improvements in pain and disability but cognitive-behavioral therapy is more effective for activity interference and depressive symptoms; (2) cognitive-behavioral therapy combined with usual treatment provides short-term benefits in pain and ability to control pain compared with usual treatment alone; (3) intraoral myofascial therapy may reduce pain and improve jaw opening; and (4) structured self-care management may be more effective than usual treatment. The evidence suggests that occlusal devices may not be effective in reducing pain and improving motion for TMD of variable duration. Evidence on the effectiveness of biofeedback is inconclusive. Discussion: The available evidence suggests that cognitive-behavioral therapy, intraoral myofascial therapy, and self-care management are therapeutic options for persistent TMD. Abstract : Supplemental Digital Content is available in the text.